Development of the TAIL rating scheme for indoor environmental quality in schools - Tran, Minh-Tien; Wei, Wenjuan; Dassonville, Claire; Mandin, Corinne; Wargocki, Pawel; Hequet, Valérie (CLIMA 2022 conference, 2022)
The TAIL rating scheme was developed to assess indoor environmental quality (IEQ) in offices and hotels undergoing deep renovation and was recently extended by the PredicTAIL method allowing prediction of IEQ through modeling. TAIL provides the methodology for rating the quality of the thermal, acoustic, and luminous environments, the indoor air quality, and the overall quality of the indoor environment. The present work is an extension of the use of TAIL rating scheme for school classrooms to provide necessary information for effective actions and mitigation measures to improve classroom IEQ. The TAIL was invented by examining the literature and certification schemes to identify the parameters that characterize IEQ in offices and hotels; 12 parameters were selected. A similarly pragmatic approach is followed when developing the TAIL for schools. The literature published after 2010 was surveyed to identify papers presenting measurements of IEQ in classrooms in Europe, the USA, and Australia; 75 papers were identified. Besides the 12 parameters already included in TAIL, the studies also used other parameters to characterize classroom IEQ. These parameters will be evaluated for their importance for the teaching, learning, and well-being of pupils, as well as measuring complexity, among others. Based on this assessment, the relevant parameters will be selected for inclusion in the TAIL rating for schools. The selection will be assisted using the measurements from the extensive campaign organized by the Indoor Air Quality Observatory in 308 schools and 602 classrooms in France; some of these data will be used to assess the efficacy of the TAIL for schools indicator. The relationships between the newly developed TAIL for schools, the teacher’s perceptions of indoor environmental quality, and detailed building characteristics will be studied.
Keywords: BE:RELEVANT; C:Australia; C:France; _z:class:countries; _z:class:themes; evidence_review_2